Avaliação de doses ocupacionais em cirurgias ortopédicas - Endlich, Larissa Lopes (2018)
The objective of the present study was measured as doses of occupational radiation at the level of the physician who performs orthopedic surgeries using a fluoroscopy device was exposed in his workday by means of a thermoluminescent dosimetry (TLD), comparing the occupational doses obtained with legislation and propose measures of radioprotection. From the monitoring carried out, after approval of the research by energy committees, between 18/12/2017 to 05/02/2018, reponses were obtained for the targetcritical points: whole body (thorax), crystalline, pneuide, right and left hands. From the average measurement values obtained for a procedure, an annual radiation dose is estimated in each of the analyzed regions and compared with a current legislation. Compared with CNEN 3.01, the effective dose estimate for the entire body (measured in the chest region) above the apron was 109 ± 86 mSv/year, four times higher than the national legislation (20,0 mSv / year), however, if the professional is considered to wear a plumbing apron (IPE) and even reduces a dose by 99,94%, an estimated dose decreased to 0,07 ± 0,05 mSv/year, being appropriate. As estimates of equivalent doses for the extremities (79 ± 55 mSv/year) and thyroid (61 ± 99 mSv/year), results are obtained under the current legislation: 500 mSv/year and 300 mSv / year for extremities and thyroid, respectively. (20 mSv/year): 79 ± 64 mSv/year. The results confirm the need to comply with the national laws in force through a monitoring program of the professional who is exposed to ionizing radiation, in addition to the use of radiation protection clothing such as apron, tire protector, gloves and goggles; focusing on the solo medical doctor, but on a whole team involved in the surgery.